2015
DOI: 10.1128/jvi.03343-14
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 70 Regulates Degradation of the Mumps Virus Phosphoprotein via the Ubiquitin-Proteasome Pathway

Abstract: Mumps virus (MuV) infection induces formation of cytoplasmic inclusion bodies (IBs). Growing evidence indicates thatIBs are the sites where RNA viruses synthesize their viral RNA. However, in the case of MuV infection, little is known about the viral and cellular compositions and biological functions of the IBs. In this study, pulldown purification and Nterminal amino acid sequencing revealed that stress-inducible heat shock protein 70 (Hsp72) was a binding partner of MuV phosphoprotein (P protein), which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 43 publications
1
41
0
Order By: Relevance
“…In addition, Hsp70 has been reported to regulate viral polymerase activity through interaction with the N proteins of MeV (45), respiratory syncytial virus (RSV) (35), and canine distemper virus (46). Hsp70 also interacts with the P proteins of MuV (47) and RSV (48). In the present study, we demonstrated that Hsp90 is required for the correct folding of the MuV L protein and that Hsp70 assists in the biogenesis of the L protein as a cochaperone of Hsp90.…”
Section: Discussionsupporting
confidence: 48%
“…In addition, Hsp70 has been reported to regulate viral polymerase activity through interaction with the N proteins of MeV (45), respiratory syncytial virus (RSV) (35), and canine distemper virus (46). Hsp70 also interacts with the P proteins of MuV (47) and RSV (48). In the present study, we demonstrated that Hsp90 is required for the correct folding of the MuV L protein and that Hsp70 assists in the biogenesis of the L protein as a cochaperone of Hsp90.…”
Section: Discussionsupporting
confidence: 48%
“…Many mononegaviruses, including vesicular stomatitis virus (41), rabies virus (42), ebolavirus (43), and mumps virus (44), produce cytoplasmic inclusion bodies (equivalent to the MV RNP complex) where viral RNA synthesis occurs. In vesicular stomatitis virus-infected cells, primary RNA synthesis takes place throughout the host cell cytoplasm, and viral protein expression redirects viral RNA synthesis to cytoplasmic inclusions (41).…”
Section: Discussionmentioning
confidence: 99%
“…Nocodazole was purchased from Sigma (St. Louis, MO). Anti-N (clone 23D), -M (clone 79D), and -HN (clone 78) mouse monoclonal antibodies (MAbs) and anti-MuV N rabbit polyclonal antibody (PAb) were prepared as described previously (33)(34)(35). Anti-␤actin (clone AC-15) and anti-␣-tubulin (clone DM1A) mouse MAbs were purchased from Sigma.…”
Section: Cells and Virusmentioning
confidence: 99%